PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Abdulloh Muzaki; Herlin Tundjung Setijaning; Julia Safitri (ITB AAS Indonesia Surakarta, 2024)
This research aims to analyze the influence of profitability, liquidity and asset structure on a company's capital structure, with company size as a moderating variable. Data is taken from diverse business sectors to provide a comprehensive view of this relationship. Regression analysis methods are used to test the influence of independent variables on the dependent variable, taking into account the moderating influence of company size. The research results show that profitability has a significant positive influence on capital structure, indicating that companies tend to use more debt when profitability increases. Liquidity also has an insignificant negative effect on capital structure, indicating that companies tend to be more conservative in using debt when liquidity is high. Furthermore, asset structure has a significant positive influence on capital structure. The company size variable moderately influences the relationship between profitability and capital structure, as well as the relationship between asset structure and capital structure, but does not moderate the relationship between liquidity and capital structure. This research provides new insights into the factors that influence corporate funding decisions and the contribution of company size in moderating the relationship between liquidity and capital structure.